Emergent factors in Eating Disorders in childhood and preadolescence - Pellicciari Alessandro; Sacrato Leonardo; Franzoni Emilio (BMC, 2010)
Abstract We have reviewed the literature related to the current advances in comprehension of Eating Disorders (ED) in childhood and preadolescence. The state of art regarding the psychodynamic models concerning the onset of ED are explained. DSM-IV and ICD-10 criteria are discussed, pointing out their little value in the characterization of early eating difficulties. Historic and new diagnostic classifications are displayed in detail. We provided a clearer description of subclinical patterns. Finally we focus on the key role of the paediatrician in detecting and managing parental concerns regarding feeding.